Observed relationships between large-scale patterns of variability and atmospheric carbon dioxide - Hawes, Amy K., author; Department of Atmospheric Science, Colorado State University, publisher (Colorado State University. Libraries, 2006)
Atmospheric carbon dioxide (CO2 has been steadily increasing for the last two hundred years, largely due to the burning of fossil fuels. The impact of increasing CO2 on global climate change has been studied extensively, but uncertainties about the effects of climate change on the sources and sinks of the global carbon cycle continue to impede our abilities to accurately predict future CO2 concentrations, and thus to fully understand the global carbon cycle. The intent of this thesis is to examine how three major patterns of large-scale variability impact changes in atmospheric CO2. Most previous studies on this topic have focused on the relationships between the El Nino Southern Oscillation (ENSO) and the global carbon cycle. However, far fewer studies have focused on the carbon cycle impacts of the other two major patterns of variability in the atmosphere, the so-called Northern and Southern Annular Modes. These patterns have substantial influences on surface conditions in their respective hemispheres, and thus are likely to have an impact on the flux of carbon at the Earth's surface. Furthermore, both patterns have also exhibited trends over the past few decades and therefore may play a role in driving long-term changes in atmospheric CO2 concentrations. We examine the impact of the Northern and Southern Annular Modes on monthly and daily mean concentrations of atmospheric CO2 at stations around the world. The results suggest both annular modes are, in fact, coupled to variations in atmospheric CO2 in a manner consistent with their climate impacts, but that the amplitudes of the relationships are generally small, particularly in the Southern Hemisphere. In the Northern Hemisphere, correlations and regressions suggest that the wintertime Northern Annular Mode (NAM) affects the springtime CO2 flux in boreal land regions. On shorter time scales, advection may largely be driving variations in local CO2 time series. In the Southern Hemisphere, the relationships are much weaker, but the results suggest that the Southern Annular Mode (SAM) is associated with variations in concentrations of CO2 over the Antarctic Peninsula. All findings are compared with results derived from surface flux estimates from the Atmospheric Tracer Transport Model Intercomparison Project (TransCom). The TransCom results are broadly consistent with the findings based on observations but show some unexpectedly strong relationships in regions far from the centers of action of the annular modes.
Spring 2006.
Keywords: Atmospheric carbon dioxide